2023
DOI: 10.1093/ptj/pzad076
|View full text |Cite
|
Sign up to set email alerts
|

Coproduction and Usability of a Smartphone App for Falls Reporting in Parkinson Disease

Abstract: Objective The purpose of this study was to coproduce a smart-phone application for digital falls reporting in people with Parkinson disease (PD) and to determine usability using an explanatory mixed-methods approach. Methods This study was undertaken in 3 phases. Phase 1 was the development phase, in which people with PD were recruited as co-researchers to the project. The researchers, alongside a project advisory group, copr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…While our discussion has mainly focused on co-production research practice, there is growing consensus that co-produced research is a critical mechanism to improve research translation and benefit clinical practice ( 4 , 48 , 49 ). To date, participatory research within rehabilitation settings has reported successful achievement of focused clinical-level outcomes, such as having lived experience involvement in clinical service and technology development ( 50 , 51 ). The challenge now for the rehabilitation research community is to engage in genuine epistemic, or knowledge, justice—founded on (but not limited to) the principles of power sharing, relationship building and adaptability ( 2 , 4 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…While our discussion has mainly focused on co-production research practice, there is growing consensus that co-produced research is a critical mechanism to improve research translation and benefit clinical practice ( 4 , 48 , 49 ). To date, participatory research within rehabilitation settings has reported successful achievement of focused clinical-level outcomes, such as having lived experience involvement in clinical service and technology development ( 50 , 51 ). The challenge now for the rehabilitation research community is to engage in genuine epistemic, or knowledge, justice—founded on (but not limited to) the principles of power sharing, relationship building and adaptability ( 2 , 4 , 52 ).…”
Section: Discussionmentioning
confidence: 99%